EXPLORATION OF CONSUMER SATISFACTION TOWARDS PRODUCT QUALITY, SERVICE AND LOCATION AT GALU RESTO IN WAWOTOBI SUB-DISTRICT, KONAWE REGENCY - Melati Melati (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to understand the level of customer satisfaction with the product quality, service, and location at Galu Resto. Located in Wawotobi, Southeast Sulawesi, Galu Resto combines a natural concept with local architecture, rice field views, and regional cuisine as key attractions for its customers. This study used a qualitative approach, using direct interviews and field observations. The results indicate that customer satisfaction is determined by several key factors: quality products made from fresh ingredients, friendly and responsive service, and a strategic location that creates an emotionally comfortable atmosphere. The research findings indicate that these three factors work synergistically, creating a dining experience that is not only functionally satisfying but also strengthens the emotional and cultural aspects of customers. Thus, Galu Resto is able to provide added value through an approach that combines local culture and a natural setting. This research is expected to provide a reference for the development of local culinary businesses with a model based on experience and cultural values.